Poza bytem i niebytem : filozofia buddyjska wobec zarzutu nihilizmu - Jakubczak, Krzysztof (Wydawnictwo Księgarnia Akademicka, 2019)
BEYOND BEING AND NON-BEING: BUDDHIST PHILOSOPHY AGAINST THE CHARGE OF NIHILISM The subject of this book is the so-called ‘Buddhist nihilism’. I refer to it as ‘so-called’ because I view the category of nihilism as relative rather than absolute. In other words, a thought can be perceived as nihilist only in relation to another contrasting affirmatory thought. The Buddha teaches in the Kātyāyana-sūtra that one should give up the categories of existence and non-existence as they lack descriptive value. Therefore, from the point of view of a theory that affirms being (i.e. recognizes that the category of being/existence has a descriptive value), the Buddha’s position may accurately be labelled as nihilism. Within that framework, the category of existence is treated as an objective one. However, this position loses its validity if it is considered from the perspective of the Buddha’s teachings. According to the view of the Middle Way, treating being/existence as an objective category is a manifestation of a cognitive error. Undermining the objectivity of existence and non-existence, the Buddha revokes nihilism and affirmatism. He achieves this on two planes – the metaphysical and the epistemological.